Correlates of Intention to Use Condom among Male Migrant Factory Workers in Northern India - S A Rizwan (Journal of Clinical and Diagnostic Research, 2014)
Objective: Consistent condom use among high-risk groups, which in turn are dependant on favourable condom use intention is important for the success of HIV/AIDS prevention programmes. We aimed to determine intention to use condom and delineate their correlates in a sample of male migrant workers in northern India. Materials and Methods: This was a cross-sectional facility based survey conducted in 2011. Inclusion criteria were: male migrant workers aged ≥18 years, who were born outside Haryana, who had moved to current location after 15 years of age, who had worked in the current factory for at least one year and who were able to give valid consent. Face-to-face interviews were conducted with semi-structured questionnaire. Since this analysis was a secondary objective of a larger migrant study, sample size was not calculated separately. Intention to use condom was measured on a five point Likert scale and expressed as a linear score (higher the score more unfavourable the intention). A linear regression analysis was performed to identify factors independently associated with unfavourable intention. Results: Mean (SD) score for intention to use condom was 10.4 (3.4). Unfavourable intention was associated with men who had migrated to greater number of places, who had lesser HIV/ AIDS knowledge, who had never used condom and who had not used condom at last non-spousal sex. The model had an adjusted R-square value of 0.63 and was statistically significant (F = 41.9, p <0.001). Conclusion: Male migrant workers had unfavourable intention to use condom. This intention could be favourably modified by behaviour change communication through already existing targeted intervention platforms, focussing attention on groups with higher mobility, lower education, lower HIV/AIDS knowledge and inconsistent condom use.